A media content sharing system. - Syed Mohamed, Syed Abd. Rahman Al-Hadad (2011)
The present invention generally relates to media sharing content system using P2P principles. The present invention provides users giving feedbacks on the streamed media content to be stored as future reference for future users who intend to stream the media content. This avoiding the users wasting time streaming the video but at the end, they are not satisfied.